IMPROVING THE STRATEGY FOR THE DEVELOPMENT OF THE OIL AND GAS INDUSTRY OF THE REPUBLIC OF UZBEKISTAN - Mamajanov Azizbek Alisher ugli (Zeta Repository, 2023)
This article discusses the issues of improving the management of oil and gas enterprises in Uzbekistan, thereby increasing the efficiency of enterprises in the industry.